Distribution of hepatitis C virus genotypes among injecting drug users in Lebanon - Mahfoud, Ziyad (BioMed Central, 2010)
BACKGROUND: The aim of this study is to determine the prevalence of anti-HCV among injecting drug users (IDUs) in Lebanon, to establish the current prevalence of HCV genotypes in this population and to determine whether demographic characteristics and behavioral variables differ between participants who were HCV-RNA positive and those who were HCV-RNA negative or between the different genotypes. Participants were recruited using respondent-driven sampling method. The blood samples were collected as dried blood spots and then eluted to be tested for HCV, HBV and HIV by ELISA. Anti-HCV positive samples were subjected to RNA extraction followed by qualitative detection and genotyping. RESULTS: Among 106 IDUs, 56 (52.8%) were anti-HCV-positive. The two groups did not differ in terms of age, marital status, and nationality. As for the behavioral variable, there was a trend of increased risky behaviors among the HCV-RNA positive group as compared to the HCV-RNA negative group but none of the variables reached statistical significance. Half (50%) of the 56 anti-HCV-positive were HCV-RNA positive. Genotype 3 was the predominant one (57.1%) followed by genotype 1 (21%) and genotype 4 (18%). CONCLUSIONS: The predominance of genotype 3 seems to be the predominant genotype among IDUs in Lebanon, a situation similar to that among IDUs in Western Europe. This study provides a base-line against possible future radical epidemiological variant that might occur in IDUs.